Effects of elevated atmospheric CO2 and mineral nitrogen deposition on litter quality, bioleaching and decomposition in a sphagnum peat bog - Siegenthaler, Andy; Mitchell, Edward; Van der Heijden, Edvin; Buttler, Alexandre; Grosvernier, Philippe; Gobat, Jean-Michel (: Springer, 1999)
A brief overview of an attempt to link the effect of elevated CO2 and nitrogen deposition on litter quality and decomposition in a Sphagnum peat bog is given. Litter of three common species (Eriophorum vaginatum, Polytrichum strictum and Sphagnum fallax) was collected from field plots after two years of pre-treatment in two parallel experiments: a) Elevated atmospheric CO2 experiment, b) mineral nitrogen fertilisation experiment. The litters were put into litterbags, leached and inserted into field plots for 3 months, where they decomposed under specific treatment. Distinction between effects of initial litter quality and decomposition on mass loss in the bioleaching and/or in field decomposition process could be tested using a particular set-up in which cross-effects of pre-treatment and treatment were considered.
, 2015
Keywords: decomposition; litter quality; elevated CO2; nitrogen deposition; bioleaching; peat bogs